Propagação in vitro de Cedrela fissilis Vell. uma espécie arbórea brasileira ameaçada de extinção - Bonfá, Yasmim Smarsaro (2019)
Cedrela fissilis Vell. (Meliaceae) is a valuable wood species from the Atlantic Forest and have been widely explored that takes it to the risk of extinction (VU category). The in vitro propagation of native forestry species presents as a viable source to reverse and alleviate this situation. Dude to the few studies available of in vitro culture of C. fissilis that associate the productivity rise with maximization of cost-benefit, this work aimed at describing a protocol for vegetative propagation of C. fissilis using micropropagation technique. For in vitro germination, it was tested the MS and B5 medium, the total concentration and half force, and half force MS medium was chosen later because of the better results of %G (82) and GSI (1.218). For micropropagation, the explants were cultivated for buds induction in MS medium supplemented with cytokinins KIN or BAP (0; 0.5; 2; 4 µM) isolatedly, and for roots induction it was used MS supplemented with auxins AIB or ANA (0; 1; 3 µM) isolatedly. The buds induction were significantly affected by the explant origin and the concentration of cytokinin used in the process. The highest scores for bud numbers (3.84) and bud length (2.2) were reached in MS without cytokinin supplementation. The rooting was reached in all treatments, with number of roots for explants being numerically higher (2.55) in the one supplemented with 3 µM AIB. The regenerated plants were acclimatazed in sterile commercial substrate, with ex vitro survival rate higher than 10% after 30 days.